ANALISIS SIFAT-SIFAT MEKANIS BETON SELF COMPACTING CONCRETE (SCC) DENGAN PENAMBAHAN FILLER ABU ECENG GONDOK - Muhamad Yusuf Khanafi; Sumirin; Kartono Wibowo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Water hyacinth is an aquatic plant considered as a pest and difficult to eradicate due to its fast growth and strong resilience. However, water hyacinth also contains high fiber content, and the ash resulting from its combustion contains silica that can be used as a concrete additive. This research aims to evaluate the influence of adding water hyacinth ash on the mechanical properties of self-compacting concrete (SCC), such as compressive strength, flexural strength, and split tensile strength. Concrete is a commonly used structural material in various construction projects, and SCC is an innovative type of concrete that can self-compact without the need for a vibrating tool. In this study, data collection was conducted through literature review from various sources, including journals, theses, books, and the internet. Additionally, laboratory testing was performed to examine the coarse and fine aggregates and determine the effects of water hyacinth ash addition on compressive strength, flexural strength, split tensile strength, and modulus of elasticity. The research findings indicate that the addition of 5% water hyacinth ash results in a decrease in compressive strength by 2.008 MPa. However, adding 10% water hyacinth ash can increase compressive strength by 1.02 MPa. Split tensile strength also experiences an increase of 0.255 MPa with a 5% addition of water hyacinth ash and an increase of 0.669 MPa with a 10% addition. On the other hand, flexural strength increases by 0.515 MPa with a 5% addition of water hyacinth ash but decreases by 1.006 MPa with a 10% addition.